CPL2 and CPL3 act redundantly in FLC activation and flowering time regulation in Arabidopsis - Yu Zhang; Lisha Shen (Plant Signaling & Behavior, 2022)
Reproductive success of plants greatly depends on the proper timing of the floral transition, which is precisely controlled by a complex genetic network. FLOWERING LOCUS C (FLC), a central floral repressor, is transcriptionally activated by the FRIGIDA (FRI) activator complex including FLC EXPRESSOR (FLX) and FLX-LIKE 4 (FLX4). C-TERMINAL DOMAIN PHOSPHATASE-LIKE 3 (CPL3) forms a protein complex with FLX and FLX4 to mediate the dephosphorylation of FLX4, thereby promoting FLC expression to repress flowering in both winter and summer annuals. Here, we show that CPL2 acts redundantly with CPL3 to mediate FLC activation and flowering time. Similar to CPL3, CPL2 inhibits the floral transition, and is required for basal FLC expression in summer annuals and FLC activation in winter annuals. CPL2 directly interacts with FLX which further bridges the interaction between CPL2 and FLX4. Our results suggest that CPL2 and CPL3 function redundantly in regulating FLC expression to prevent precocious flowering.